Adoption by lesbians and gay men : a new dimension in family diversity - Brodzinsky, David; Pertman, Adam. (Oxford ; New York : Oxford University Press, 2012)
The practice of adoption has changed dramatically over the past half century, with profound implications for children and families. Perhaps the most remarkable and controversial transformation during this time has been the growing willingness of adoption professionals to place children with sexual-minority individuals and couples. Yet, despite considerable research showing that lesbians and gay men can make good parents, they continue to experience difficulties and barriers in many parts of the country in their efforts to adopt and raise children. Indeed, while progress in this area has been significant, it has been impeded by the homophobia and heterosexist attitudes of adoption professionals and the judiciary; by numerous stereotypes and misconceptions about parenting by lesbians and gay men, and by a lack of adequate guidelines and training for establishing best practice standards in working with this rapidly growing group of adoptive parents. This work explores the gamut of historical, legal, sociological, psychological, social casework, and personal issues related to adoption by sexual-minority individuals and couples. Leading experts in a variety of fields address, and often shatter, the controversies, myths, and misconceptions hindering efforts by these individuals to adopt and raise children. It provides insights and specific recommendations for establishing empirically validated best practices for working with an important sector of our society, for treating all prospective and current parents fairly and equally, and, perhaps most importantly, for increasing a still largely untapped resource for providing families for children who need them.
American adoption: a brief history / Cynthia Russett -- Emerging diversity in family life: adoption by gay and lesbian parents / Adam Pertman and Jeanne Howard -- Legal issues in lesbian and gay adoption / Annette R. Appell -- Adoption by lesbians and gay men: a national survey of adoption agency policies and practices / David M. Brodzinsky -- Adolescents with same-sex parents: findings from the National Longitudinal Study of Adolescent Health / Charlotte J. Patterson and Jennifer L. Wainright -- Planned lesbian families: a review of the U.S. National Longitudinal Lesbian Family Study / Nanette Gartrell, Heidi Peyser, and Henry Bos -- Lesbian and gay prospective foster and adoptive families: the homestudy assessment process / Gerald P. Mallon -- Supporting gay and lesbian adoptive families before and after adoption / Devon Brooks, Hansung Kim, and Leslie H. Wind -- Gay and lesbian adoptive parents: stressors and strengths / Scott Ryan and Suzanne Brown -- Lesbian and gay adoptive parent families: assessment, clinical issues, and intervention / Abbie E. Goldberg and Mark Gianino -- Adoption by lesbians and gay men: what we know, need to know, and ought to do / David M. Brodzinsky, Robert-Jay Green, and Katie Katuzny.
Includes bibliographical references and indexes.
Keywords: Gay adoption -- United States; Gay parents -- United States; Lesbian mothers -- United States